The Purpose Driven Church : Growth Without Compromising Your Message & Mission - Warren, Richard, 1954- (Grand Rapids, Mich. : Zondervan Pub., 1995)
"The Purpose-Driven(r) Church has brought focus and direction to more pastors and church leaders than you can count. What a gift!"--John Ortberg, bestselling author Every church is driven by something. Tradition, finances, programs, personalities, events, seekers, and even buildings can each be the controlling force in a church. But Rick Warren believes that in order for a church to be healthy it must become a purpose-driven church, built around the five New Testament purposes given to the church by Jesus. "The issue is church health, not church growth!" declares Warren. "If your church is healthy, growth will occur naturally. Healthy, consistent growth is the result of balancing the five biblical purposes of the church." Rick Warren shares a proven five-part strategy that will enable your church to grow warmer through fellowship, deeper through discipleship, stronger through worship, broader through ministry, larger through evangelism. The Purpose-Driven(r) Church shifts the focus away from church building programs to emphasizing a people-building process. Warren says, "If you will concentrate on building people, God will build the church." -- publisher's description.
Forward / W. A. Criswell -- Surfing spiritual waves -- The Saddleback story -- Myths about growing churches -- What drives your church? -- The foundation for a healthy church -- Defining your purposes -- Communicating your purposes -- Organizing around your purposes -- Applying your purposes -- Who is your target? -- Knowing whom you can best reach -- Developing your strategy -- How Jesus attracted crowds -- Worship can be a witness -- Designing a seeker-sensitive service -- Selecting your music -- Preaching to the unchurched -- Turning attenders into members (congregation) -- Developing mature members (committed) -- Turning members into ministers (core) -- God's purpose for your church.
Includes bibliographical references.
Keywords: Church growth; Evangelistic work